2020
DOI: 10.3390/rs12010126
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Forage Quality of Grasslands Using UAV-Borne Imaging Spectroscopy

Abstract: The timely knowledge of forage quality of grasslands is vital for matching the demands in animal feeding. Remote sensing (RS) is a promising tool for estimating field-scale forage quality compared with traditional methods, which usually do not provide equally detailed information. However, the applicability of RS prediction models depends on the variability of the underlying calibration data, which can be brought about by the inclusion of a multitude of grassland types and management practices in the model dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 52 publications
3
65
0
Order By: Relevance
“…The support vector machine (SVM) is another successful algorithm and has been widely used with a Gaussian kernel function [39], and it could be used as a benchmark with RF. Some previous studies reported that the Cubist algorithm was superior to RF in predicting LAI [40] and SVM for estimating acid detergent fibre in forage [41]. In addition, Stochastic Gradient Boosting (SGB) also has been applied to biomass estimation, and its high performance has been reported [42].…”
Section: Introductionmentioning
confidence: 99%
“…The support vector machine (SVM) is another successful algorithm and has been widely used with a Gaussian kernel function [39], and it could be used as a benchmark with RF. Some previous studies reported that the Cubist algorithm was superior to RF in predicting LAI [40] and SVM for estimating acid detergent fibre in forage [41]. In addition, Stochastic Gradient Boosting (SGB) also has been applied to biomass estimation, and its high performance has been reported [42].…”
Section: Introductionmentioning
confidence: 99%
“…Benefits and limitations exist with all techniques, but UAVs whether alone or in fusion with other techniques promise to be a major enabling technology. The scientific literature over the past few years shows emerging benefits from UAV-captured photogrammetric, multispectral and hyperspectral imaging of pasture condition with examples from the USA, Brazil, Europe, Australia and South Africa [13][14][15][16]. An optimum solution using data fusion possibly exists, combining the best aspects of all technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Crude protein and ADF are two commonly used indicators of pasture digestion. Recent UAV studies have demonstrated the use of hyperspectral sensing in detecting both crude protein and ADF in the natural pastures of other countries [15]. UAV hyperspectral sensors are not low-cost; however, for nutrient estimation they are essential.…”
Section: Introductionmentioning
confidence: 99%
“…Parameters listed are (ADF), ash, dry matter (DM), crude protein (CP), in vivo dry matter digestibility (IVDMD), neutral detergent fibre (NDF) and water-soluble carbohydrates (WSC). References [59][60][61] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%